1995
DOI: 10.1002/j.1460-2075.1995.tb00104.x
|View full text |Cite
|
Sign up to set email alerts
|

The Polycomb-group gene, extra sex combs, encodes a nuclear member of the WD-40 repeat family.

Abstract: We have delimited the extra sex combs (esc) gene to < 4 kb that include a single transcript and are able to rescue both the maternal and zygotic esc phenotypes. Several mutations have been identified within the esc transcript. In agreement with earlier genetic studies, esc is expressed maternally and its product is most abundant during the early embryonic stages. It encodes a protein of the WD‐40 repeat family, which localizes predominantly to the nucleus. During germ band extension, it is expressed in a stere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 87 publications
2
90
0
Order By: Relevance
“…As already reported for mouse EED, a specific feature of the HEED protein was the occurrence of several repeats of the module GH-(30 -40 residue spacer)-WD (46), now simply referred to as WD repeat motif (47). In HEED (Fig.…”
Section: Isolation Of a Human Homolog Of Murine Eed (Heed) By Interacmentioning
confidence: 66%
“…As already reported for mouse EED, a specific feature of the HEED protein was the occurrence of several repeats of the module GH-(30 -40 residue spacer)-WD (46), now simply referred to as WD repeat motif (47). In HEED (Fig.…”
Section: Isolation Of a Human Homolog Of Murine Eed (Heed) By Interacmentioning
confidence: 66%
“…Initially recruited, although not in a direct interaction (Kehle et al, 1998; Zhang et al, 1998), by a zinc finger transcription factor (HUNCHBACK), ESC functions transiently (Struhl and Brower, 1992;Gutjahr et al, 1995;Sathe and Harte, 1995) to recruit other polycomb group proteins, including the SET domain protein E(Z), which form large, stable complexes at specific sites within the genome (Sewalt et al, 1998;van der Vlag and Otte, 1999;Ng et al, 2000). The complexes, perhaps by the action of a histone deacetylase component (van der Vlag and Otte, 1999), are thought to remodel chromatin into a condensed form that prevents gene transcription (Pirrotta, 1998).…”
Section: Molecular Function Of the Fie Proteinmentioning
confidence: 99%
“…The Drosophila and mouse WD and SET domain polycomb proteins have a somatic role and control pattern formation during embryogenesis by suppressing the transcription of homeotic genes (Gutjahr et al, 1995;Schumacher et al, 1996). In contrast, the Caenorhabditis WD and SET domain homologs MES6 and MES2, respectively, act as transcriptional repressors (Kelly and Fire, 1998) and are essential for germ line development (Holdemann et al, 1998;Korf et al, 1998).…”
Section: Function Of Fie In the Female Gametophytementioning
confidence: 99%
See 1 more Smart Citation
“…However, an increasing number of WD repeat proteins have been identified that are nuclear localized and function in the repression of transcription. These include Tup1, Hir1, and Met30 in S. cerevisiae; SCON2 in Neurospora crassa; extra sex combs and groucho in Drosophila; COP1 in Arabidopsis thaliana; and HIRA and the family of TLE proteins in humans (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). These WD repeat repressor proteins turn off a wide variety of genes, including those involved in segmentation, sex determination, and neurogenesis (controlled by groucho) and those involved in photomorphogenesis (controlled by COP1) (7,11).…”
mentioning
confidence: 99%